Activated Microglia in Cortical White Matter Across Cognitive Aging Trajectories - Gefen, Tamar; Kim, Garam; Bolbolan, Kabriya; Geoly, Andrew; Ohm, Daniel; Oboudiyat, Carly; Shahidehpour, Ryan; Rademaker, Alfred; Weintraub, Sandra; Bigio, Eileen H.; Mesulam, M.-Marsel; Rogalski, Emily; et al. (Frontiers in Aging Neuroscience, 2019)
Activation of microglia, the primary mediators of inflammation in the brain, is a major component of gliosis and neuronal loss in a number of age-related neurodegenerative disorders, such as Alzheimer disease. The role of activated microglia in white matter, and its relationship to cognitive decline during aging, are unknown. The current study evaluated microglia densities in white matter of postmortem specimens from cognitively normal young adults, cognitively normal older adults, and cognitive “SuperAgers”, a unique group of individuals over age 80 whose memory test scores are at a level equal to or better than scores of 50-to-65-year-olds. Specimens from cognitively-normal old, young, and “SuperAgers” were cut into whole hemisphere sections and immunohistochemical procedures were used to visualize activated microglia with HLA-DR antibody. Densities of HLA-DR-positive activated microglia underlying five cortical regions were evaluated. Statistical findings showed a significant main effect of group on differences in microglia density where cognitively-normal old showed highest densities; no difference between SuperAgers and young specimens were detected. In two autopsied SuperAgers with MRI FLAIR available, prominent hyperintensities in periventricular regions were observed, and interestingly, examination of corresponding postmortem sections showed only sparse microglia densities. In conclusion, activated microglia appear to respond to age-related pathologic changes in cortical white matter, and this phenomenon is largely spared in SuperAgers. Findings offer insights into the relationship between white matter neuroinflammatory changes and cognitive integrity during aging.